NALAR TEOLOGI ISLAM DI ERA GLOBALISASI - Ermagusti Ermagusti (Turast: Jurnal Penelitian dan Pengabdian, 2021)
Discussions of Islamic theology often seem classic, only focusing on the metaphysical-transidental-normative area, without facing a future that is full of challenges and hopes. Even though science and technology have progressed far and wide through the intricacies of human life, the reality is that the discussion of Islamic theology still does not give satisfaction and peace to the soul, because it has not touched the present and the future. The strategic role of theological studies in Islam socio-culturally, namely the role of providing explanations that can be clearly understood and able to give deep meaning to the development of science and technology. Actually, what is offered by Islamic theology is to invite Muslims to be open and think rationally, because theology is basically rational thinking that cannot be separated from the control of revelation. Therefore, Islamic theologians review their thoughts and ideas again, what kind of theological concept is suitable in this era of globalization. As an answer, sunnatullah theology with its rational philosophy of life is oriented to the world in addition to the hereafter, it also makes Muslims productive in their fields of life.